2019
DOI: 10.2147/ndt.s216874
|View full text |Cite
|
Sign up to set email alerts
|

<p>Electroacupuncture Promoting Axonal Regeneration in Spinal Cord Injury Rats via Suppression of Nogo/NgR and Rho/ROCK Signaling Pathway</p>

Abstract: To observe the changes of Nogo/NgR and Rho/ROCK signaling pathway-related gene and protein expression in rats with spinal cord injury (SCI) treated with electroacupuncture (EA) and to further investigate the possible mechanism of EA for treating SCI. Methods: Allen's method was used to create the SCI rat model. Sixty-four model rats were further subdivided into four subgroups, namely, the SCI model group (SCI), EA treatment group (EA), blocking agent Y27632 treatment group (Y27632) and EA+blocking agent Y27632… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“… 27 In addition, studies have confirmed that Nogo-A and NgR expression levels are increased after SCI. 19 Furthermore, Nogo-A affects nerve function recovery after SCI in primates. 20 Therefore, reduction of Nogo-A and NgR expression is crucial to promote recovery of the injured spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“… 27 In addition, studies have confirmed that Nogo-A and NgR expression levels are increased after SCI. 19 Furthermore, Nogo-A affects nerve function recovery after SCI in primates. 20 Therefore, reduction of Nogo-A and NgR expression is crucial to promote recovery of the injured spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…2 Hz-30 min B Xiao [23] 64 Male 200 ± 20 g T10 2 Hz-20 min C Yan [24] 36 Female 220-250 g T10 2 Hz-20 min A Zhang [25] 80 Male 230-270 g T10 20 Hz-30 min A Zhang [26] 54 Male 250 ± 20 g T9-T11 2 Hz-30 min B Zhao [27] 96 All -T8-9 2 Hz-30 min A Zheng [28] 48 Male 180-220 g L5 100 Hz-1 min A Zhu [29] 24 Male 180-220 g T10 2 Hz-30 min A 3 BioMed Research International…”
Section: Data Extractionmentioning
confidence: 99%
“…Gao et al reported that HSP 90 participates in electroacupuncture-induced analgesia in chronic neuropathic pain ( Gao et al, 2021 ). Other signaling pathways, such as PI3K/Akt/Erk, Nogo/NgR, Rho/ROCK, and mTOR, may also include the acupuncture-related beneficial effects against SCI ( Renfu et al, 2014 ; Wei et al, 2018 ; Xiao et al, 2019 ; Li et al, 2020 ).…”
Section: Mechanism Of Acupuncture Therapy In Spinal Cord Injurymentioning
confidence: 99%